Discurso pronunciado en público en el aula - Agata Komorowska (Universitat de València, 2016)
En el artículo se presentan las ventajas de utilizar el discurso público como material para el aprendizaje y perfeccionamiento del español como lengua extranjera, destinado a diversos niveles del dominio lingüístico. Partiendo de las características del aprendiz, se brindan varias propuestas de actividades para realizar con la finalidad de mejorar su competencia comunicativa. Palabras clave: discurso público, competencia comunicativa, perfeccionamiento ELE.   Dicourse pronounced in public in the classroom Abstract: This article presents the advantages of using public discourse as a material for learning and improving Spanish as a foreign language skills. The activities here presented are designed for different levels of language proficiency. Based on the learner's characteristics, several proposals for activities are provided in order to improve his/her communicative competence. Keywords: public speaking, communication skills, improvement ELE.